Penerapan Sanksi Pidana Denda Sebagai Upaya Menekan Tingkat Pelanggaran Lalu Lintas di Kota Ternate - M. Agus F Sudarsono; Faissal Malik; Anshar Anshar (Khairun Law Journal, 2020)
The legal basis regulating traffic is Law of the Republic of Indonesia Number 22 of 2009 concerning "Road Traffic and Transportation" (hereinafter written UULAJ). Traffic procedures are regulated in Article 105 to Article 126 UULAJ. However, the current high number of traffic violations is one of the causes of the high number of traffic accidents that occur. With the increasing need for transportation for the community, there are also more vehicles in the traffic lane so that it cannot be denied that it will cause violations to be committed, especially by motorized vehicle drivers which results in quite difficult and complicated problems. Fines are a type of crime that is generally imposed on all violations. The fact is currently happening in Kota Ternate, although the ticket fines already exist, the number of traffic violations is always there and tends to increase. One of the causes is the low number of fines imposed by the District Court Judges of Ternate on traffic offenders so that traffic offenders feel that they are able to pay the sanctions given and the supervision of traffic officers is not proportional to the size of the area being supervised so that it causes unevenness and weakness. supervision of offendersSanctions; Criminal Fines; Traffic violations